SOSIALISASI PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN COVID-19 KEPADA MASYARAKAT NELAYAN DI PESISIR KUALA BUBON KABUPATEN ACEH BARAT - Mohamad Gazali; Zuriat Zuriat; Amarullah Amarullah; M. Ali Sarong; Endah Anisa Rahma; Mai Suriani; Rina Syafitri; Sulaiman Ali (Jurnal Marine Kreatif, 2020)
Corona virus (COVID-19) is a type of deadly virus with a fast spreading process. This virus infects the human respiratory tract. To prevent the spread of COVID-19, all activities must follow the health protocols published by the Indonesian Ministry of Health, such as social distancing, wearing masks and washing hands. The aim of this study is to provide understanding to the Kuala Bubon fishing community regarding health protocols as an effort to prevent COVID-19 and to provide touchless hand washer assistance to make it easier for people to do health protocols. This study which is a part of community service activity was conducted by using the lecture/mentoring method. The output of the activity is an increase of public awareness to always follow health protocols to every activity. The activity received a positive response from the local community. This can be seen from the enthusiasm of the community in participating in this community service activity.